PENGARUH LIKUIDITAS, PROFITABILITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN - Tindaon, Aldy Yefta (Jurnal Manajemen dan Profesional, 2024)
This research aims to analyze the influence of liquidity, profitability and solvency on share prices in banking companies. The sample for this research consists of 33 companies listed on the Indonesial Stock Exchange (BEI) to submit their financial reports for the 2021-2023 period. The data used in this research is secondary datal and the sample selection used the purposive sampling method. The analytical tool used is multiple linear regression analysis. The results of hypothesis testing show that liquidity and solvency have no effect on stock prices, while profitability has effect on stock prices.